Predictors and oncological outcomes of achieving Pentafecta in radical cystectomy: a meta-analysis - Zeng, Zhiqiang; Chen, Wubin; Chen, Wangbing; Zou, Lunhong; Li, Tao; Zhou, Tao; Zhao, Huan; Hu, Xionglin; Ji, Peng; He, Yang; Zhou, Yubo (Frontiers in Oncology, 2026)
ObjectiveThis study aims to evaluate the predictive value of RC-Pentafecta on overall survival (OS) and cancer-specific survival (CSS) after radical cystectomy (RC) through meta-analysis and to explore the perioperative predictors of RC-Pentafecta.MethodThis systematic review and meta-analysis were conducted in accordance with the PRISMA statement. We systematically searched PubMed, Embase, Cochrane Library, and Web of Science databases and included 9 retrospective studies from 2020 to 2025. The fixed effect model and random effect model were used for combined analysis.ResultsThe results of the study showed that patients who achieved RC-Pentafecta had significantly better OS and CSS than those who did not. In addition, Age, length of hospital stay (LOS), American Association of Medical Sciences Anesthesiology (ASA) score, diabetes mellitus, hypertension, Type of Urinary diversion (UD), pathological T-stage (pT), and pathological N-stage (pN) showed significant differences among the groups that achieved RC-Pentafecta.ConclusionsRC-Pentafecta is a valuable criterion that can effectively predict OS and CSS in patients after RC. Age, perioperative health status, and pathological stage are important predictors of RC-Pentafecta.